The Role Of Khitobah Practice In Enhancing Santri's Self-Confidence And Public Speaking Skills - Muhammad Nashirul Umam; Aniqoh (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Public speaking skills and self-confidence are essential competencies that santri (Islamic boarding school students) need to develop as preparation for fulfilling their roles in Islamic preaching (da'wah) and community life. However, some santri still experience nervousness, lack self-confidence, rely heavily on written speech scripts, and are unable to deliver their presentations systematically during khitobah (speech practice) activities. This study aims to describe the implementation of khitobah practice, analyze its role in enhancing the self-confidence and public speaking skills of santri, and identify the supporting and inhibiting factors affecting its effectiveness at Nurul Muttaqin Kemiri Islamic Boarding School. This study employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation and were analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The findings indicate that khitobah practice is conducted regularly through a rotational assignment system accompanied by continuous guidance and evaluation. The practice contributes to improving santri's self-confidence, as reflected in their increased willingness to speak in public and reduced nervousness. It also enhances their public speaking skills in terms of intonation, articulation, mastery of the material, fluency of delivery, and eye contact. The effectiveness of the program is supported by encouragement from student administrators, structured mentoring, regular evaluation, opportunities for public performance, and a conducive learning environment. Meanwhile, shyness, speaking anxiety, limited experience, and technical constraints constitute the primary inhibiting factors. This study confirms that khitobah practice represents a form of experiential learning that contributes to the development of santri's self-confidence and public speaking skills and may serve as a reference for the development of communication training programs in Islamic boarding schools.